2014
DOI: 10.1177/216507991406200104
|View full text |Cite
|
Sign up to set email alerts
|

Resident Aggression toward Staff at a Center for the Developmentally Disabled

Abstract: Few studies have examined factors contributing to nonfatal assaults to staff working in residential care facilities. The authors evaluated resident assaults toward direct care/nursing staff at an Intermediate Care Facility for Individuals with Mental Retardation (ICF/MR), which included observations of work areas, employee interviews, calculation of injury and assault rates for 2004 to 2007 from Occupational Safety and Health Administration Logs, and review of state ICF/MR guidelines. Most staff interviewed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The implication is that non-physical forms of abuse should not be considered as less serious than physical assault. The high prevalence rate for violence, per se, suggested the lack of any formal violence prevention program being in place [ 38 ], disturbingly suggesting a cultural acceptance of violence, including a lack of administrative support to address WPV within healthcare settings [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The implication is that non-physical forms of abuse should not be considered as less serious than physical assault. The high prevalence rate for violence, per se, suggested the lack of any formal violence prevention program being in place [ 38 ], disturbingly suggesting a cultural acceptance of violence, including a lack of administrative support to address WPV within healthcare settings [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In professional nurses, physical health factors, such as immobility, deterioration in self-care and usual activities, pain or discomfort, and psychological health factors, such as anxiety or depression, were associated with stress. West, Galloway and Niemeier ( 2014 ) also emphasised that nurses who have repeated contact with intellectually disabled persons place themselves at risk for injury because of assault and occupational injuries such as musculoskeletal disorders. There is also the risk of transmission of blood-borne pathogens through fingernail scratches, and saliva, for example, hepatitis B and C. Bites also pose a potential risk of infection from the patient to the nursing staff.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nurses’ involvement in the care of these patients was affected because of their fear of engaging with such patients and getting hurt. West et al ( 2014 ) found that 83% of mental health nurses were injured while engaged in the physical restraint of aggressive patients, of which 50% reported seeing health care practitioners for their injuries and 46% requested time off from work because of injuries. Violence is therefore an area that needs urgent attention and its management is important in providing a safe and therapeutic environment in intellectually disabled settings (Currid 2009 ).…”
Section: Literature Reviewmentioning
confidence: 99%